Does the change from conventional circular to linear stapling in proximal gastric bypass surgery affect long-term quality of life?. (1st June 2022) - Teixeira, H; Teuben, M P J; Teuber, H; Hauswirth, F; Probst, P; Müller, M K
Abstract: Objective: The continuous desire to improve bariatric surgery outcomes, and therefore patient satisfaction, leads to a constant search for new surgical approaches. Every change in a well-established protocol needs to undergo evaluation and its benefit for patients must be demonstrated. With respect to technical changes in bariatric surgery, long-term effects on quality of life have not yet been studied. We analyzed quality of life scores and clinical outcomes at a single bariatric center transitioning from circular to a linear bypass protocol. Methods: Between June 2012 and March 2016, 235 patients were included in this retrospective study from a prospectively collected database. Two groups were compared. Group CBP included those patients treated with a circular stapling bypass protocol (n=117). This protocol was primarily used in 2012. Between 2013 and 2015 a transition period occurred. Thereafter, the linear stapling bypass protocol (Group LBP, n=118) was primarily utilized. Quality of life (QoL) was assessed with the Moorehead-Ardelt QoL score, which was gathered preoperatively, and at 1, 2, and 5 years after surgery. Results: Quality of life scores improved significantly after intervention in both study groups. The most prominent improvement was seen within the first year after surgery. There were no statistically significant differences between the groups. During the first two years, quality of life score improvement occurred independently of achieved weight loss, whereas a correlation between QoL-improvement and reported weight loss was identified between 24 and 60 months postoperatively (r2 0.112, p<0.001). Further, complications had no impact on change in QoL scores. Conclusion: Quality of life scores assessed by the Moorehead-Ardelt QoL questionnaire were, independent of operative technique and postoperative weight loss, significantly improved in the first two years after gastric bypass surgery. Thereafter, QoL scores showed lasting improvement in correlation with further weight loss.